A scoping review on the risk of tuberculosis in specific population groups: can we expand the World Health Organization recommendations?. (11th January 2023) - Bigio, Jacob; Viscardi, Angelo; Gore, Genevieve; Matteelli, Alberto; Sulis, Giorgia
Since 2015, the World Health Organization (WHO) has recommended prioritising testing and treatment of tuberculosis (TB) infection (TBI) in 11 high-risk groups. With new options emerging for TB preventive treatment, we conducted a scoping review, in consultation with the WHO's Global Tuberculosis Programme, to explore the evidence for other population groups at potentially high risk of progression to active TB. We searched six databases for preprints and articles published between 2000 and August 2022. 18 out of 33 668 screened records were included (six meta-analyses and 12 original research studies). Most were observational studies reporting the incidence of active TB in a risk group versus control. Glomerular diseases had the strongest association with active TB (standardised incidence ratio 23.36, 95% CI 16.76–31.68) based on an unpublished study. Other conditions associated with increased risk of active TB included hepatitis C, malignancies, diabetes mellitus, rheumatoid arthritis and vitamin D deficiency. Corticosteroid use was also associated with increased risk in several studies, although heterogeneous definitions of exposure and indications for use challenge interpretation. Despite methodological limitations of the identified studies, expanding the recommendations for TBI screening and treatment to new risk groups such as those reported here should be considered. Further group-specific systematic reviews may provide additional data for decision-making. Recommendations to test for and treat tuberculosis infection are currently limited to 11 high-risk groups. Our review suggests that new evidence is available on other potential at-risk populations that might deserve updated recommendations from the WHO. https://bit.ly/3VCE5Qi